The Impact of Sharia Fintech and People's Business Credit (KUR) on the Sustainability of MSMEs in Mataram City - Safina; Nur Fitri Hidayanti; Zaenafi Ariani; Mukhlishin (Universitas Bangka Belitung, 2025)
This study aims to analyse the impact of Sharia Fintech and People's Business Credit (KUR) on the sustainability of MSMEs in Mataram City. This study is important because MSMEs still have limited access to financing, so the use of technology-based financial services and subsidised credit programmes is necessary to support business continuity. The study uses a quantitative approach with a survey method of 100 MSME actors selected through purposive sampling. The research instrument is a questionnaire with a 1–5 Likert scale, which is then analysed using multiple linear regression through SPSS version 22. The results show that Sharia Fintech has a positive and significant effect on the sustainability of MSMEs, as reflected in increased access to financing, operational efficiency, and innovation capabilities. In addition, KUR also has a positive and significant effect on the sustainability of MSMEs through capital strengthening, increased production capacity, and improved business stability. Simultaneously, both variables were proven to contribute significantly to the sustainability of MSMEs in Mataram City. Thus, it can be concluded that the integration of Sharia-based technology financing and government credit programmes can improve the sustainability performance of MSMEs and has the potential to become a strategic instrument in local economic development.